Formation of the aesthetics of social realism in the literatures of the Turkic-speaking peoples (Eurasian Journal of Philology Science and Education, 2023)
The purpose of this article is to study the processes of formation of the aesthetics of socialist realism in the literatures of the Turkic-speaking peoples of the former Soviet republics.Socialist realism, as a trend in the literature of the twentieth century, first began to take shape in Russian literature in the pre-Soviet era - in the populist, and later in the so-called proletarian literature. The policy of nationalization of literature during the establishment of Soviet power required a unified aesthetic system in literature. These requirements corresponded to the direction, which was called socialist realism by the Chairman of the Organizing Committee of the Writers' Union of the USSR I. Gronsky in 1932. The formation of the aesthetics of socialist realism in Russian literature was due to both the artistic phenomena of literature and the official doctrine of the Soviet state. In the literatures of the Turkic-speaking peoples of the former USSR, social realism, as a literary trend, arose as a result of the policy of nationalization of literature. For many centuries, the literature of these peoples relied on the general Turkic spiritual-religious and cultural-mythological foundation, in the period from the 11th to the 19th centuries it developed in the context of Eastern classical literature.The literature of the Turkic-speaking peoples of the former USSR during the formation of the aesthetics of socialist realism rather resembled epigone literature. However, the system of images, plot configurations of works, compositional and architectonic forms differed significantly from Russian Soviet literature. The authors relied on the traditions of oral folk art and classical oriental literature. Key words: aesthetics of socialist realism, literature of the Turkic-speaking peoples, policy of nationalization of literature, epigone literature.